Еволюція промислової власності - Муренко, Олена Леонідівна (Право, 2015)
У статті розкрита тема походження такого поняття, як інтелектуальна власність, а також досліджено процес розвитку патентно-правової системи, як основи охорони цього виду власності. У процесі розгляду вищезгаданого питання визначено чітку відмінність між такими категоріями, як «привілей» і «патент». Крім того, відзначено важливість розробленого Венеціанською Республікою Патентного Кодексу 1474 р., положення якого і на сьогоднішній день простежуються в патентному законодавстві багатьох країн світу.

This article analyses the concept of intellectual property and traces its evolution. In particular, the various features of intellectual property are considered. Each feature brings material or other benefit (profit, increase the products competitiveness, development of citizens etc.). The article also shows reasons for the protection of intellectual property rights. It is said that in a period of rapid development of the factory in the 14th century, the royal power was granting special privileges for the first time in England – the predecessor of the patent. The advantages that each of the parties received are described : the royal power; monarch, which slapped a privilege; the person who invented and used innovations. Monarch was providing inventors with an exclusive right to use this technology, giving the inventor a competitive advantage. On the other hand disadvantages of benefits are considered, since with time the invention privileges became means for feudal lords enrichment, and not for inventors stimulation. The article reveals the turning point in the development of intellectual property rights (1628), when Regulation on monopolies was adopted which granted exclusive rights to the first inventor of a product (privilege was given for 14 years). The second part of the article analyses specific types of intellectual property – patents and trademarks. The article draws attention to the issues related to the patent legal framework development and the stages of the Patent Code development worldwide. The article conclusion emphasizes the importance of the original legislation and laws that were passed in the 14–15 century, since many provisions of the Patent Code (1474) still work nowadays.
Evolution of industrial property
Keywords: власність інтелектуальна; суверен; патент; законодавство; знак товарний; Патентний Кодекс; intellectual property; sovereign privilege; patent law; trademark; Patent Code